Feasibility of Biomass Briquette Production from Municipal Waste Streams by Integrating the Informal Sector in the Philippines - Aries Roda D. Romallosa (Resources, 2017)
A technical and socio-economic feasibility study of biomass briquette production was performed in Iloilo City, Philippines, by integrating a registered group of the informal sector. The study has shown that the simulated production of biomass briquettes obtained from the municipal waste stream could lead to a feasible on-site fuel production line after determining its usability, quality and applicability to the would-be users. The technology utilized for briquetting is not complicated when operated due to its simple, yet sturdy design with suggestive results in terms of production rate, bulk density and heating value of the briquettes produced. Quality briquettes were created from mixtures of waste paper, sawdust and carbonized rice husk, making these material flows a renewable source of cost-effective fuels. An informal sector that would venture into briquette production can be considered profitable for small business enterprising, as demonstrated in the study. The informal sector from other parts of the world, having similar conditionality with that of the Uswag Calajunan Livelihood Association, Inc. (UCLA), could play a significant role in the recovery of these reusable waste materials from the waste stream and can add value to them as alternative fuels and raw materials (AFR) for household energy supply using appropriate technologies.